Terminology - clarifying the current confusion and presenting the correct terminology - Ansari, Ejaz (Frontiers in Ophthalmology, 2023)
Most readers will be familiar with terminology (from meetings and conferences) that we, the editors, would deem to be incorrect or confusing. In general, we all tend to accept the information conveyed to us without really questioning what the terms truly mean. Therefore, the subsequent chapters discussing the IOLs in question should be studied with this in mind since a lot of familiar terminology will be used in those chapters, which, strictly speaking, may not be in line with the most accurate terminology and classification.